Laboratory Work Package with Authentic Assessment to Develop Collaborative Performance Skills of Physics Education Students - Khoiri, Nur; Rusilawati, Ani; Wiyanto, Wiyanto; Sulhadi, Sulhadi; Susilawati, Susilawati (KnE Social Sciences, 2019)
Electromotive force is one of the abstract subjects that require laboratory work for better understanding of its concepts. This research aims to develop a package of electromotive force laboratory work using authentic assessment. The other beneﬁt expected is that students experience collaborative performance skills. The method is research and development in order to get expert recommendation on the feasibility of a laboratory work package for induced electromotive force and the use of its results. Hence, the expected outcome of this research is a package of laboratory work on induced electromotive force. Results of data analyses show that experts recommend the use of induced electromotive force laboratory work package as a medium in the learning process as it comes with meaningful experiences. These results show that students performing the laboratory work package on induced electromotive force understand the concept better and they also learn collaborative performance skills. Keywords: induced electromotive force, collaborative performance skills